Multi-omics landscape of Interferon-stimulated gene OASL reveals a potential biomarker in pan-cancer: from prognosis to tumor microenvironment - Liu, Yi; Yang, Runyu; Zhang, Mengyao; Yang, Bingyu; Du, Yue; Feng, Hui; Wang, Wenjuan; Xue, Busheng; Niu, Fan; He, Pengcheng (Frontiers in Immunology, 2024)
Background: OASL (Oligoadenylate Synthetase-Like), an interferon-induced protein in the OAS family, plays a significant role in anti-viral response. Studies have demonstrated its association with prognosis of certain tumors. However, the mechanism through which OASL affects tumors is unclear. A systemic pan-cancer study of OASL needs to be illustrated.Methods: Analysis of OASL expression across 33 tumors was conducted utilizing TCGA, GTEx and CPTAC databases. COX and Log-Rank regressions were employed to calculate the prognosis. We validated the impact of OASL on apoptosis, migration, and invasion in pancreatic cancer cell lines. Moreover, we employed seven algorithms in bulk data to investigate the association of OASL expression and immune cell infiltration within tumor immune microenvironment (TIME) and ultimately validated at single-cell transcriptome level.We discovered elevated expression of OASL and its genetic heterogeneity in certain tumors, which link closely to prognosis. Validation experiments were conducted in PAAD and confirmed these findings. Additionally, OASL regulates immune checkpoint ligand such as programmed death ligand 1 (PD-L1), through IFN-γ/STAT1 and IL-6/JAK/STAT3 pathways in tumor cells. Meanwhile, OASL affects macrophages infiltration in TIME. By these mechanisms OASL could cause dysfunction of cytotoxic T lymphocytes (CTLs) in tumors. Discussion: Multi-omics analysis reveals OASL as a prognostic and immunological biomarker in pan-cancer.